Characteristics of L-PRP preparations for treating Achilles tendon rupture within the PATH-2 study. (17th February 2021) - Harrison, Paul; Didembourg, Marie; Wood, Alexander; Devi, Amarpreet; Dinsdale, Robert; Hazeldine, Jon; Alsousou, Joseph; Keene, David J; Hulley, Philippa; Wagland, Susan; Parsons, Scott; Thompson, Jacqueline; et al.
Abstract: Platelet-rich plasma (PRP) is an autologous preparation that has been claimed to improve healing and mechanobiological properties of tendons both in vitro and in vivo. In this sub-study from the PATH-2 (PRP in Achilles Tendon Healing-2) trial, we report the cellular and growth factor content and quality of the Leukocyte-rich PRP (L-PRP) (N = 103) prepared using a standardized commercial preparation method across 19 different UK centers. Baseline whole blood cell counts (red cells, leukocyte and platelets) demonstrated that the two groups were well-matched. L-PRP analysis gave a mean platelet count of 852.6 x 10 9 /L (SD 438.96), a mean leukocyte cell count of 15.13 x 10 9 /L (SD 10.28) and a mean red blood cell count of 0.91 x 10 12 /L (SD 1.49). The activation status of the L-PRP gave either low or high expression levels of the degranulation marker CD62p before and after ex-vivo platelet activation respectively. TGF-β, VEGF, PDGF, IGF and FGFb mean concentrations were 131.92 ng/ml, 0.98 ng/ml, 55.34 ng/ml, 78.2 ng/ml and 111.0 pg/ml respectively with expected correlations with both platelet and leukocyte counts. While PATH-2 results demonstrated that there was no evidence L-PRP is effective for improving clinical outcomes at 24 weeks after Achilles tendon rupture, our findings support that the majority of L-PRP properties were within the method specification and performance.